Patient Medical Record Information System as Big Data Implementation with NIK in Tegal City Health Service - Arif Rakhman; Umriaty (Institute of Computer Science (IOCS), 2020)
The advancement of health technology that is fast and accurate is increasingly becoming the main requirement of decision-makers. Hospitals, clinics, health centers as institutions that store so much data also require correct and precise data processing that can be presented in the form of reports. Meanwhile, keeping traditional medical record files requires a large area and is prone to the impact of natural disasters and fires. According to patient's point of view, the physical documents of medical records such as medical cards, X-rays, ultrasound results, ECG results and others also have a risk of being lost or damaged and so that it becomes troublesome. With a modified Borg and Gall model development procedure, the products produced by the medical record application are functioned to facilitate the performance health center staffs and doctors, as well as to be more effective and efficient system and integrated NIK data